FUKUSHIMA FALLOUT IN SAKHALIN REGION, RUSSIA, PART 2: 137Cs AND 134Cs IN GRASSLAND VEGETATION - V. P. Ramzaev; A. N. Barkovsky; A. V. Gromov; S. A. Ivanov; M. V. Kaduka (Радиационная гигиена)
Samples of vegetation (vascular plants) were collected at 14 grasslands on Kunashir, Iturup, Urup and Paramushir Islands in August–September 2012. All surveyed grasslands were virgin lands with respect to Fukushima fallout. Four plots were used as pastures for cattle in 2012. About 1 kg of green vegetation (mixed grass-forb crop) was taken from each of 13 plots. Seven samples of wormwood (Artemisia sp.) and three samples of Kuril dwarf bamboo (Sasa sp.) of the same mass were collected for comparison. A density of the above ground biomass was estimated at one of the plots. Activities of 134Cs and 137Cs radionuclides were determined by direct γ-ray spectrometry method using HP-germanium detectors. Inventories of 134Cs and 137Cs in the top 20 cm layer of soil were estimated by the authors earlier for each of these 14 plots based of the soil samples analysis. Caesium-134, a marker of Fukushima fallout, was determined in 18 of 24 vegetation samples. Caesium-137 activity was quantified in all of 24 samples. The activity concentration of the radionuclides in plants (wet weight) ranged from <0.05 Bq kg−1 to 1.6 Bq kg-1 for 134Cs and from 0.06 Bq kg−1 to 5.8 Bq kg-1 for 137Cs. About 2/5 (median = 41%, n = 18) of the total activity of 137Cs in plants was associated with the Fukushima accident. The soil-to-plant aggregated transfer coefficient (Tag) values in mixed grass-forb crop ranged from <0.2 × 10–3 m2 kg-1 to 11 × 10–3 m2 kg-1 for 134Cs and from 0.08 × 10–3 m2 kg-1 to 3.3 × 10–3 m2 kg-1 for 137Cs. The Tag values for 134Cs were statistically significantly higher compared to the Tag values for 137Cs. The median Tag for 134Cs in mixed grass-forb crop decreased in the 2011–2012 period by a factor of about two: from 12 × 10–3 m2 kg-1 to 6.6 × 10–3 m2 kg-1. The ecological half-time, Teco, of 134Cs in the plants was approximately one year. In 2011–2012, the median Tag for pre-Fukushima 137Cs in mixed grass-forb crop was estimated as 0.12 × 10–3 m2 kg-1. This value is lower by a factor of 100 and 50 compared to the median values of Tag that were deduced for Fukushima-derived radiocaesium in 2011 and 2012, respectively. The radiocaesium Tag values for Sasa sp. and Artemisia sp. agreed with those for mixed grass-forb crop. At grasslands with the aboveground biomass density of 1 kg m–2 and the Tag of 6 × 10–3 m2 kg-1 for 134Cs, the contribution of the vegetation contamination to total inventory of the radionuclide did not exceed 1%. For 137Cs, this contribution was less than 0.1%.